Effect Of Moringa oleifera Extract Gel on Macrophage Cells in Diabetic Traumatic Ulcer Healing - Raziv Ganesha; I Gusti Ngurah Putra Dermawan; Ni Nyoman Gemini Sari; Agung Wira Trystano Kepakisan (Fakultas Kedokteran Gigi, Universitas Mahasaraswati Denpasar, 2026)
Introduction: Traumatic ulcers are common oral mucosal lesions caused by mechanical injury. In diabetes, wound healing is delayed due to impaired immune responses, including macrophage dysfunction. Moringa oleifera leaves contain flavonoids, tannins, phenols, and saponins that have anti-inflammatory and wound-healing properties. This study evaluated the effect of Moringa oleifera extract gel on macrophage cell counts during traumatic ulcer healing in diabetic male Wistar rats. Materials and Methods: This experimental study used a post-test-only control group design with 32 male Wistar rats. Diabetes was induced using streptozotocin (STZ). Traumatic ulcers were created on the labial mucosa using a burnisher. Rats were divided into four treatment groups (P1–P4) receiving Moringa oleifera extract gel and four control groups (K1–K4) receiving 3% Na-CMC gel. Observations were conducted on days 3, 5, 7, and 9. Gel was applied three times daily. Tissue samples were processed histologically, stained with hematoxylin-eosin, and examined for macrophage counts. Results: Mean macrophage counts in treatment groups were P1=11.45, P2=10.15, P3=12.33, and P4=10.28, while control groups were K1=5.65, K2=6.70, K3=7.65, and K4=10.25. One-Way ANOVA showed significant differences among groups (p=0.021). Tukey Post Hoc analysis revealed a significant difference between P3 and K1 (p=0.037). Pearson correlation showed a significant negative correlation (r=-0.357; p=0.045). Conclusion: Moringa oleifera extract gel significantly affected macrophage cell counts during traumatic ulcer healing in diabetic male Wistar rats.